The Green Revolution and the Gene Revolution in Pakistan: Policy Implications (The Quaid-i-Azam Memorial Lecture) (The Pakistan Development Review, 2005)
Pakistan achieved high levels of Green Revolution Modern Variety (GRMV) adoption in the Green Revolution. Pakistan out-performed India and Bangladesh in the Green Revolution. Only China, among major countries, out-performed Pakistan in the Green Revolution. Pakistan does not have the food safety and environmental risk studies in place to support a regulatory environment for biotechnology. In effect, Pakistan is following the “precautionary principle” and applying it to science policy. This paper argues that this is a mistake. Pakistan is paying a “double penalty” for its inability to develop the regulatory systems required to take advantage of genetically modified (GM) crops. Not only does it lose the cost reductions enabled by GM crops, but because other countries have adopted GM crops, world prices are lower as a result and affect Pakistan’s export crops.